2010
DOI: 10.1007/s10439-010-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of Elastic, Poroelastic, and Osmotic Tissue Properties of Intervertebral Disks to Analyze Behavior in Compression

Abstract: Intervertebral disks support compressive forces because of their elastic stiffness as well as the fluid pressures resulting from poroelasticity and the osmotic (swelling) effects. Analytical methods can quantify the relative contributions, but only if correct material properties are used. To identify appropriate tissue properties, an experimental study and finite element analytical simulation of poroelastic and osmotic behavior of intervertebral disks were combined to refine published values of disk and endpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
(54 reference statements)
0
23
1
Order By: Relevance
“…The increase in water uptake and disc height recovery with hypoosmotic pressure agrees well with data in the literature. 13,27 Mechanical loading 13 and loading from osmotic pressure during recovery hinder fluid-flow into the disc and disc height recovery (Figure 2A). For example, disc recovery in the 1.5 M PBS group exhibited features of loading after 4 hours of recovery, suggesting a change in fluid-flow direction from inflow to outflow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in water uptake and disc height recovery with hypoosmotic pressure agrees well with data in the literature. 13,27 Mechanical loading 13 and loading from osmotic pressure during recovery hinder fluid-flow into the disc and disc height recovery (Figure 2A). For example, disc recovery in the 1.5 M PBS group exhibited features of loading after 4 hours of recovery, suggesting a change in fluid-flow direction from inflow to outflow.…”
Section: Discussionmentioning
confidence: 99%
“…3,23,25 -27 Stokes and coworkers observed a decrease in joint stiffness with an increase in water uptake during stress-relaxation (constant applied displacement). 27 Vergroesen et al 24 demonstrated that the effect of osmotic pressure on water absorption was highly dependent on magnitude of the applied load. However, it is not clear how osmotic pressure affects disc recovery behavior under low loading conditions that simulate bed-rest conditions.…”
mentioning
confidence: 99%
“…Varying the external osmolarity is an important approach to investigate the contribution of fixed charges to the overall mechanical function of the tissue. Stokes et al [57] studied the response of human lumbar disks under constant compressive strain, in bath with varying saline concentrations. They observed that varying of external osmolarity from low to high causes a stress relaxation phenomenon.…”
Section: Bending and Torsion Testmentioning
confidence: 99%
“…Recently, interest has grown in attempts at quantitative assessment of tissue hydration using BIS in many disease states [1,2,3]. In addition, the tissue response to stress in the setting of edema has recently been the subject of study as a quantitative tool for edema assessment [4,5,6]. The examination for early stage/pitting peripheral edema has been performed for centuries by grasping and pressing on the patient's extremity.…”
Section: Introductionmentioning
confidence: 99%